Dating documents by chromatographic analysis of dyes present in viscous and liquid inks. (29th March 2019) - Mouquinho, Ana; Gameiro, Rui; Ferreira, Carla; Quintas, Alexandre; Bernardo, Alexandra
Abstract : Introduction: Determining the ink age in a document has always been a complex challenge in forensic sciences [1 ]. To determine the time since deposition (TSD) of an ink, factors such as the physical and chemical properties of the paper (support), the storage conditions, as well as the physical-chemical of ink processes after deposition on paper must be considered [2 ]. Ink aging process involves specifically solvent evaporation, dye degradation, polymerization and hardening of the resins [3 ]. The aim of this work is to develop analytical methodologies that allow the determination of the time of ink deposition through the characterization of the dyes chemical changes. Materials and methods: Linear liquid and viscous ink´s pens samples of 4 cm were cut from an ink entry of recent deposition (T0) and a 5 months' deposition (T5) samples. Paper ink extraction was performed using 120 µL of methanol with the help of an ultrasonic bath and vortexed at 1400 rpm at 35 °C. The total extraction time was 40 min. For the quantitative analysis, 20 µL of O-cresol was added to each sample to be used as an internal standard. Chromatographic analyses were executed with HPLC/DAD (Eclipse XDB-C8 5 µm 4, 6 × 150 mm) at 25° C and a flow rate of 0, 8 mL/min. Samples were eluted with a gradient system: 80% in a buffer solution of NH4 HCO2 pH 4 and 20% in CH3 CN as an initial condition, finishing with 0% in a buffer solution of NH4 HCO2 after 32 min. Chromatograms samples were monitored at 590 and 273 nm. Results: The chromatograms revealed that the two types of inks under analysis have different profiles. Moreover, the chromatogram of inks under study changes with time. Concerning the preliminary results, in the case of viscous inks, at 590 nm, the chromatogram shows three peaks at T0 (tr = 18, 18 min, tr = 16, 59 min and tr = 14, 99 min) and two peaks at T5 (tr = 18, 17 min and tr = 16, 57 min). The peaks of tr = 18, 18min and tr = 16, 57min decrease by about 44% and 39% in 5 months, respectively. For the liquid ink samples, it is possible to identify only two chromatographic peaks (tr = 18, 22 min and tr = 16, 61 min). Discussion and conclusions: Preliminary chromatographic results suggest that it is possible to discriminate a liquid (2 peaks) from a viscous ink (3 peaks) as well as distinguishing time since deposition (TSD) for the viscous inks. From the analysis of chromatograms and spectra, it is possible to obtain qualitative and quantitative chemical information of the different dyes in inks and use this information to use the study of dyes to dating inks. The methodology under development is promising to discriminate ink types and time since deposition of an in on a paper. However, more data must be gathered.